수분오염에 따른 경유의 연료적 특성 - 임영관(Young-Kwan Lim); 원기요(Ki-Yoe Won); 강병석(Byung-Seok Kang); 박소휘(So-Hwi Park); 박장민(Jang-Min Park); 강대혁(Dea-Hyuk Kang) (Tribology and Lubricants, 2020)
It rains heavily, such as long rain and typhoons, during a typical rainy season in Korea. In this season, several fuel contamination accidents by water and vehicular problems caused by water contaminated fuel occur. Many research groups have studied the effects of water contaminated fuel on vehicles and environment. However the characteristics of water contaminated fuel have not been studied. In this study, we prepared diesel samples with a constant ratio of water (0~30 volume %) using an emulsifier. Then, we analyzed these diesel samples for their representative fuel properties. In the analytical results, diesel with 30% water showed an increase in fuel properties such as density (823→883 kg/㎥), kinematic viscosity (2.601→6.345 ㎟/s), flash point (47→56℃), pour point (-22→2℃), CFPP (cold filter plugging point) (-17→20℃) and copper corrosion number (1a→2a). The low temperature characteristics, such as low pour point and CFPP, blocks the fuel filter in the cold season. In addition, water contaminated diesel decreases lubricity (190→410 ㎛) under high frequency reciprocating rig (HFRR) and derived cetane number (54.81→34.25). The low lubricity of fuel causes vehicle problem such as pump and injector damage owing to severe friction. In addition, the low cetane diesel fuel increases exhaust gases such as NOx and particulate matters (PM) owing to incomplete combustion. This study can be used to identify the problems caused by water contamination to vehicle and fuel facilities.